Optimizing the growth of forage and grain legumes on low pH soils through the application of superior Rhizobium leguminosarum biovar viciae strains. (25th March 2021) - Yates, Ron J.; Steel, Emma J.; Poole, Chris M.; Harrison, Robert J.; Edwards, Tom J.; Hackney, Belinda F.; Stagg, Georgina R.; Howieson, John G.
Abstract: Climate variability and current farming practices have led to declining soil fertility and pH, with a heavy reliance on fertilizers and herbicides. The addition of forage and grain legumes to farming systems not only improves soil health but also increases farm profitability through nitrogen (N) fertilizer cost offsets. However, the formation of effective symbioses between legumes and rhizobia can be unreliable and is considered at risk when combined with dry sowing practices such as those that have been designed to obviate effects of climate change. This research was initiated to improve the robustness of the legume/rhizobia symbiosis in low pH, infertile and dry soils. Production from two cultivars of field pea ( Pisum sativum ) and two species of vetch ( Vicia spp.), and symbiotic outcomes when inoculated with a range of experimental rhizobial strains ( Rhizobium leguminosarum biovar viciae), was assessed in broad acre field trials which simulated farmer practice. New rhizobia strains increased nodulation, N fixation, produced more biomass and higher seed yield than comparator commercial strains. Strain WSM4643 also demonstrated superior survival when desiccated compared to current commercial strains in the laboratory and on seed when delivered as inoculant in peat carriers. WSM4643 is a suitable prospect for a commercial inoculant in Australia and other agricultural areas of the world where growing peas and vetch on soils generally considered problematic for this legume/rhizobia symbiosis. A particular advantage of WSM4643 may be that it potentiates sowing inoculated legumes into dry soil, which is a contemporary response by farmers to climate variation.